2021
DOI: 10.3390/biomedicines10010007
|View full text |Cite
|
Sign up to set email alerts
|

ALDH1A3 Segregated Expression and Nucleus-Associated Proteasomal Degradation Are Common Traits of Glioblastoma Stem Cells

Abstract: Aldehyde dehydrogenase 1 isoforms A1 and A3 have been implicated as functional biomarkers associated with distinct molecular subtypes of glioblastoma and glioblastoma stem cells. However, the exact roles of these isoforms in different types of glioma cells remain unclear. The purpose of this study was to dissect the association of A1 or A3 isoforms with stem and non-stem glioblastoma cells. This study has undertaken a systematic characterization of A1 and A3 proteins in glioblastoma tissues and a panel of glio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…And in TNBCs and basal‐like subtypes, cancer cells have higher levels of ALDH1A3 expression, implying the prognostic value of ALDH1A3 in breast cancer patients 147 . Interestingly, ALDH1A3 is highly expressed in mesenchymal glioma stem‐like cells (Mes‐GSCs) with a more aggressive phenotype, and the inhibition of ALDH1A3 attenuates the growth of Mes‐GSCs and sensitizes Mes‐GSCs to radiotherapy, suggesting that ALDH1A3 is a promising biomarker for Mes‐GSCs 17,148–150 . Mechanistically, forkhead box D1 protein triggers self‐renewal and tumorigenicity of Mes‐GSCs both in vitro and in vivo by regulating the transcriptional activity of ALDH1A3 150 .…”
Section: Aldhs As Csc and Prognosis Markers In Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…And in TNBCs and basal‐like subtypes, cancer cells have higher levels of ALDH1A3 expression, implying the prognostic value of ALDH1A3 in breast cancer patients 147 . Interestingly, ALDH1A3 is highly expressed in mesenchymal glioma stem‐like cells (Mes‐GSCs) with a more aggressive phenotype, and the inhibition of ALDH1A3 attenuates the growth of Mes‐GSCs and sensitizes Mes‐GSCs to radiotherapy, suggesting that ALDH1A3 is a promising biomarker for Mes‐GSCs 17,148–150 . Mechanistically, forkhead box D1 protein triggers self‐renewal and tumorigenicity of Mes‐GSCs both in vitro and in vivo by regulating the transcriptional activity of ALDH1A3 150 .…”
Section: Aldhs As Csc and Prognosis Markers In Tumorsmentioning
confidence: 99%
“…147 Interestingly, ALDH1A3 is highly expressed in mesenchymal glioma stem-like cells (Mes-GSCs) with a more aggressive phenotype, and the inhibition of ALDH1A3 attenuates the growth of Mes-GSCs and sensitizes Mes-GSCs to radiotherapy, suggesting that ALDH1A3 is a promising biomarker for Mes-GSCs. 17,[148][149][150] Mechanistically, forkhead box D1 protein triggers self-renewal and tumorigenicity of Mes-GSCs both in vitro and in vivo by regulating the transcriptional activity of ALDH1A3. 150 Further studies indicate that ALDH1A1 or ALDH1A3 as markers of GSCs may be correlated with distinct molecular subtypes of highgrade glioma (HGG) tumors, with ALDH1A3 being a marker of the mesenchymal subtype 17,150,151 and ALDH1A1 being a marker of the classical subtype.…”
Section: Aldh1mentioning
confidence: 99%
“…The results were compared to the online databases of the DSMZ and Cellosaurus (Eurofins Genomics Europe). Patient-derived GSC lines used in this study were established as previously described and have been well characterized in previous studies, in terms of their stem cell frequency (SCF) and expression of various GSC markers [28,[31][32][33]. Additional information regarding their origin, SCF, predominant phenotype (Nestin +/− , GFAP +/− ), and percentage of CD133-positive cells, as well as an exemplary analysis of the GSC markers, CD133, platelet-derived growth factor receptor alpha (PDGFR-α), and aldehyde dehydrogenase 1 family member A3 (ALDH1A3), can be found in Figure S1 [28,33,34].…”
Section: Cell Culturementioning
confidence: 99%
“…Our observation that heterologous GSCs vary in their levels of GARP/GARP NU+ (Figures 1 and S8) prompted us to check if this is a mere reflection of intertumoral diversity, GARP/GARP NU+ association with a particular GSC subtype or cellular state, or a hierarchical diversification taking place during tumor growth. To address these questions, we made use of isogenic GSCs (lines IT-726-#1, IT-726-#2, IT-726-#3a, IT-726-#3b, and IT-726-#4) that have been isolated from different regions of the same tumor (Figure S9-Cohort 2"-comparison line 1) and provide a unique model for analyzing the impact of intratumoral heterogeneity in an isogenic background [31,32]. Indeed, despite their identical genetic background, isogenic GSCs from the IT-726 set displayed notable morphological differences, considerable variations in their self-renewal capacity, and expression of GSC-associated markers CD133, ALDH1 A3, and PDGFR-α (Figure S1) [31,32].…”
Section: Intratumoral Heterogeneity Of Subcellular Distribution Patte...mentioning
confidence: 99%
“…In recent years, a large number of studies have shown that ALDH1 is also closely related to other solid tumors.The overexpression of ALDH1 is associated with a poor prognosis and malignant tumor development, such as melanoma ( 204 ), glioma ( 205 ), prostate cancer ( 206 , 207 ), endometrial cancer ( 6 , 208 ), bladder cancer ( 209 ), Osteosarcoma ( 210 ), pancreatic cancer ( 211 , 212 ), kidney cancer ( 213 ), etc. ALDH1, overexpressed in melanoma, promotes tumor angiogenesis mainly by activating IL-8/Notch signaling ( 214 ).…”
Section: Aldh1 and Various Solid Tumorsmentioning
confidence: 99%